Writing, directing, and producing documentary Films and videos / Alan Rosenthal - Rosenthal, Alan
As Alan Rosenthal states in the preface to this new edition of his acclaimed resource for filmmakers, Writing, Directing, and Producing Documentary Films and Videos is “a book about storytelling—how to tell great and moving stories about fascinating people, whether they be villains or heroes.”